Manajemen Dakwah Dalam Meningkatkan Solidaritas Dan Kerukunan Pemuda - S. Fathiyatul Jannah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The aim of the research is to carry out da'wah management in increasing solidarity and harmony by the youth association of Langdulang Sana Tengah, Pasean, Pamekasan. This research uses a qualitative approach, while this type of research is phenomenological. Data collection techniques: interviews with the head of the youth association, the administrators of the youth association and members of the youth association; observation and documentation of youth association activities. Data processing techniques: data reduction, data presentation, and drawing conclusions. Checking the validity of the data: continuous observation, peer checking, as well as data source triangulation and thecnic triangulation. The results of the research show that (1) da'wah activities carried out to increase youth solidarity and harmony include sports activities such as volleyball and religious activities such as reading the Qur'an, tahlilan, reading shalawat and fadlu prayers in congregation, (2) implementing da'wah management by formulating activities, forming management, objectives, time, as well as location and costs, dividing work, involving all administrators, and assessing the da'wah activities that have been carried out.